Efektivitas Terapi Kombinasi Akupresur (Lv3, Li4) Dengan Potensi Minyak Kulit Jeruk (Citrus Sinensis) Dan Minyak Sereh (Cymbopogon Nardus) Terhadap Hipertensi - Hardini, Sandra; Trisnadewi, Eliza (Stikes Syedza Saintika Padang, 2024)
Hypertension is a health issue that requires special attention. If uncontrolled, it puts patients at high risk for heart disease, stroke, kidney failure, and other severe conditions. The incidence of hypertension in Padang City is 46.7%. Hypertension is usually controlled pharmacologically through diuretics, beta-blockers, ACE inhibitors, or calcium channel blockers. Long-term use of antihypertensive drugs can affect metabolic aspects, worsen serum lipids, and reduce glucose tolerance. Acupressure therapy on LV3 and LI4 points stimulates specific meridian points in the body using fingers to influence particular organs and activate energy flow in the body. The combination of orange peel oil and lemongrass oil induces a relaxing effect, warming the body and improving blood flow. This study aims to determine the effectiveness of combining acupressure therapy with orange peel oil and lemongrass oil in reducing hypertension. The research uses a quasi-experimental design with a two-group pretest and posttest design. The sample consisted of 16 hypertensive patients. The results showed a significant difference between the pretest and posttest, with systolic blood pressure reduced by 16.07 mmHg and diastolic by 10.69 mmHg. It can be concluded that orange peel oil (Citrus sinensis) and lemongrass oil (Cymbopogon nardus) effectively lower hypertension.Keywords: Hypertension; Acupressure LV3; LI4; Citrus sinensis; Cymbopogon nardus